Proust's Lesbianism - Ladenson, Elisabeth (Book collections on Project MUSE., 2018)
For Decades, Elisabeth Ladenson says, critics have misread or ignored a crucial element in Marcel Proust's fiction - his representation of lesbians. Her challenging new book definitively establishes the centrality of lesbianism as sexual obsession and aesthetic model in Proust's vast novel A la recherche du temps perdu.